Fuzzy-Set Qualitative Comparative Analysis: Studi Kasus Index Kebahagiaan di Indonesia Tahun 2021 - Erna Suprihartiningsih; Abdul Chalid Ahmad; Chairullah Amin (Universitas Mataram, 2023)
The happiness index provides a subjective picture of the level of community welfare. The purpose of this study is to compare the level of happiness in provinces throughout Indonesia in 2021. The analytical method used is Fuzzy-set Qualitatite Comparative Analysis with the help of fsQCA software. The results of the research through Truth Table Analysis show that the model formed is sufficient to state that the existing condition data is able to explain the outcome of happiness. Poverty, HDI, Unemployment Rate, and Gini Ratio meet the requirements of adequacy (sufficient) to explain the outcome.